Heart valve surgery: EuroSCORE vs. EuroSCORE II vs. Society of Thoracic Surgeons score - Rabbani, Muhammad Sharoz (Heart Int, 2014)
BACKGROUND: This is a validation study comparing the European System for Cardiac Operative Risk Evaluation (EuroSCORE) II with the previous additive (AES) and logistic EuroSCORE (LES) and the Society of Thoracic Surgeons’ (STS) risk prediction algorithm, for patients undergoing valve replacement with or without bypass in Pakistan. PATIENTS AND METHODS: Clinical data of 576 patients undergoing valve replacement surgery between 2006 and 2013 were retrospectively collected and individual expected risks of death were calculated by all four risk prediction algorithms. Performance of these risk algorithms was evaluated in terms of discrimination and calibration. RESULTS: There were 28 deaths (4.8%) among 576 patients, which was lower than the predicted mortality of 5.16%, 6.96% and 4.94% by AES, LES and EuroSCORE II but was higher than 2.13% predicted by STS scoring system. For single and double valve replacement procedures, EuroSCORE II was the best predictor of mortality with highest Hosmer and Lemmeshow test (H-L) p value (0.346 to 0.689) and area under the receiver operating characteristic (ROC) curve (0.637 to 0.898). For valve plus concomitant coronary artery bypass grafting (CABG) patients actual mortality was 1.88%. STS calculator came out to be the best predictor of mortality for this subgroup with H-L p value (0.480 to 0.884) and ROC (0.657 to 0.775). CONCLUSIONS: For Pakistani population EuroSCORE II is an accurate predictor for individual operative risk in patients undergoing isolated valve surgery, whereas STS performs better in the valve plus CABG group.